Performances of plantlets from selected cassava (Manihot esculenta Crantz) genotypes under Semi-Autotrophic Hydroponics (SAH) using different substrates - Mamy, B.M.; Kokou, K.; Sikirou, M.; Adetoro, N.; Angelique, K.; Nyende, A.B. (African Journals Online, 2023)
The cassava seed system faces challenges due to limited seed stock caused by a slow propagation rate and a lengthy growth period. Conventional methods lacking phytosanitary guarantees further compound these issues. To address these limitations, the Semi-Autotrophic Hydroponics (SAH) technology was adopted for the rapid mass propagation of healthy, disease-free cassava plants. This research aimed to evaluate the performance of cassava planting materials using different substrates for stem-cutting multiplication in the laboratory at the IITA Kalambo research station in DR Congo. The experiment followed a split-plot design of five replications of three consecutive sub-culture periods lasting four weeks each. Four different genotypes: IB961089A, MM060083, Nase14, and Albert28 as the main plots, with four different substrates: KlasmannTS3, Vermiculite, Local Peat, and Sawdust as the sub-plots, were laid out. Cuttings were placed in 500-ml substrate-filled boxes and watered weekly with a 100-ml Miracle-Gro solution. Data were collected on survival, height, leaf and internode numbers, and cutting numbers at the end of each subculture period. The data were analysed using ANOVA in R software. The Fisher's Least Significant Difference (LSD) test was utilised to separate means when significant differences among treatments were present (p <0.05). The results showed that survival was primarily influenced by the substrate used, with KlasmannTS3 demonstrating the highest rate, exceeding 90%. Significant differences (p < 0.05) among genotypes for survival rate and performance parameters mentioned above (p < 0.001) were observed. Similarly, there were significant differences (p < 0.001) among substrates for survival rate and performance parameters. Furthermore, the interaction between genotype and substrate significantly (p < 0.001) affected performance parameters. MM060083 performed the best across all traits. KlasmannTS3 was the superior substrate and had the highest average cutting number regardless of genotype, with a notable increase of 292% from 20 to 58.4 cuttings, representing a ratio of 1:3 within three months. Sawdust had the lowest multiplication rate, with a 5% decrease. The superior performance of KlasmannTS3 was attributed to its rapid growth and favourable properties. The interaction between MM060083 and KlasmannTS3 consistently showed the highest number of cuttings (70.4). Sawdust consistently showed poor growth performance, regardless of genotype. The study concludes that the SAH offers the potential for rapid multiplication of disease-free cassava planting materials in reduced space and time.